Современные тенденции в развитии образования в Республике Казахстан - Ашимбетова, Р. Д. (My University, 2016)
he relevance of the article is in consideration of modern trends in the sphere of the Republic of Kazakhstan education for system description of the current situation in it. The article used the analytical- descriptive method. The work focuses on the necessity for integration of education processes and upbringing to achieve the desired result that is a harmoniously developed school graduate. In this case teachers also need to be aware of the implementation of the principle of learning through the whole life. As a conclusion, the idea that interactive learning is the trend of modern adult education is proposed.
Keywords: education system; trends; information; constructive learning; interactive learning